(NiSTORIQ LINGWISTI^ESKIH U^ENIJ(B. (NdREWNIJ MIR(B.s - (NdESNICKAQ a(B. (Nw(B., (NkACNELXSON s(B. (Nd(B.s ((NlENINGRADs (NnAUKAs, 1980)
(Nw KNIGU WO[LI PUBLIKACII PO ISTORII LINGWISTI^ESKIH U^ENIJ W PERIOD DREWNEGO MIRA(B: (NwAWILONA(B, (NHETTOW(B, (NDREWNEJ iNDII I kITAQ(B. (Na TAKVE ANTI^NOSTI(B: (NaRISTOTELX(B, (NpLATON I DR(B..s
Keywords: Linguistics